2019
DOI: 10.1002/ajim.23065
|View full text |Cite
|
Sign up to set email alerts
|

Total disability days in interprovincial and home‐province workers injured in Alberta, Canada: A mixed‐methods study with matched‐pair analysis of compensation data and participant interviews

Abstract: IntroductionWorkers moving between states or provinces to find employment are reported to take longer to return to work after the injury.MethodsThe Alberta Workers Compensation Board (WCB) identified all workers from four Canadian Atlantic provinces who sustained a work injury in Alberta resulting in greater than 5 total temporary disability days (TTDDays) from January 2015 to June 2017. Each was matched on sex, age, and injury date with an Alberta claimant also with greater than 5 TTDDays. WCB information ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Previous research found that out-of-province workers from Atlantic Canada working in AB were half as likely to transition off disability benefits than their matched within-province counterparts [7].…”
Section: Interpretation Of Findingsmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous research found that out-of-province workers from Atlantic Canada working in AB were half as likely to transition off disability benefits than their matched within-province counterparts [7].…”
Section: Interpretation Of Findingsmentioning
confidence: 92%
“…Previous research using claims data has shown that out-of-province workers are different to withinprovince workers in terms of their demographic, employment and injury characteristics [7]. In order to produce unbiased estimates of the effect of out-of-province status on work disability duration, a matching strategy was used to balance the two groups on observable characteristics.…”
Section: Matching Out-of-province Claims With Within-province Claimsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 This may be due to there being limited or no data available to identify such workers but also because they make up a small number of workers and therefore a small number of potential workers' compensation claims. Although there are studies examining differences in work disability duration by interjurisdictional status in Canada, 9,10 and the United States, 11 to date, the only research on the risk of work-related injury or illness is limited to a select groups of out-of-province workers to the province of Alberta, Canada, 5 and health behaviors of fly-in, fly-out (FIFO) workers in Australia. 12 In Alberta, Canada, a combination of workers' compensation data and survey data has been used to show how workers from outside of the province are less likely to report injuries to the workers' compensation board and less likely to have accepted claims, even after adjusting for various individual and work characteristics.…”
mentioning
confidence: 99%